A novel analytical method for d-glucosamine quantification and its application in the analysis of chitosan degradation by a minimal enzyme cocktail. (4th October 2016) - Mekasha, Sophanit; Toupalová, Hana; Linggadjaja, Eka; Tolani, Harish A.; Anděra, Ladislav; Arntzen, Magnus Ø.; Vaaje-Kolstad, Gustav; Eijsink, Vincent G.H.; Agger, Jane W.
Abstract: Enzymatic depolymerization of chitosan, a β-(1, 4)-linked polycationic polysaccharide composed ofd -glucosamine (GlcN) and N -acetyl-d -glucosamine (GlcNAc) provides a possible route to the exploitation of chitin-rich biomass. Complete conversion of chitosan to mono-sugars requires the synergistic action of endo- and exo- chitosanases. In the present study we have developed an efficient and cost-effective chitosan-degrading enzyme cocktail containing only two enzymes, an endo-attacking bacterial chitosanase, Sc Csn46A, from Streptomyces coelicolor, and an exo-attacking glucosamine specific β-glucosaminidase, Tk -Glm, from the archaeon Thermococcus kodakarensis KOD1. Moreover, we developed a fast, reliable quantitative method for analysis of GlcN using high performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). The sensitivity of this method is high and less than 50 pmol was easily detected, which is about 1000-fold better than the sensitivity of more commonly used detection methods based on refractive index. We also obtained qualitative insight into product development during the enzymatic degradation reaction by means of ElectroSpray Ionization-Mass Spectrometry (ESI-MS). Graphical abstract: Highlights: Enzymatic degradation of chitosan by a two-component enzyme mixture. Quantitative analysis of glucosamine by HP-anion exchange chromatography. Exploitation of a glucosamine specific hexosaminidase. Complete product profiling by mass spectroscopy.